Alterations in the Biochemical Content in the Foot of a Freshwater Snail, Indoplanorbis exustus Exposed to Heavy Metals - Kulkarni2, H.Z. Patil1, P.N. Mahale1* and A.B. (Journal of Experimental Sciences, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> On exposure to sub lethal concentration (0.1 ppm) of Mercuric chloride & (2.00 ppm) of Zinc sulphate for 1, 7 & 14 days, Indoplanorbis exustus showed significant decrease in the level of glycogen, significant rise in the level of protein & in-significant decline in the level of lipids. The effect was more pronounced in Mercuric chloride exposure than Zinc sulphate exposure.